Cells Control BIN1-Mediated Membrane Tubulation by Altering the Membrane Charge. Issue 4 (14th February 2020) - Gowrisankaran, Sindhuja; Wang, Zuoneng; Morgan, David G.; Milosevic, Ira; Mim, Carsten
Abstract: The Bridging integrator 1 (BIN1)/Amphiphysin/Rvs (BAR) protein family is an essential part of the cell's machinery to bend membranes. BIN1 is a muscle-enriched BAR protein with an established role in muscle development and skeletal myopathies. Here, we demonstrate that BIN1, on its own, is able to form complex interconnected tubular systems in vitro, reminiscent of t-tubule system in muscle cells. We further describe how BIN1's electrostatic interactions regulate membrane bending: the ratio of negatively charged lipids in the bilayer altered membrane bending and binding properties of BIN1 and so did the manipulation of BIN1's surface charge. We show that the electrostatically mediated BIN1 membrane binding depended on the membrane curvature—it was less affected in liposomes with high curvature. Curiously, BIN1 membrane binding and bending was diminished in cells where the membrane's charge was experimentally reduced. Membrane bending was also reduced in BIN1 mutants where negative or positive charges in the BAR domain have been eliminated. This phenotype, characteristic of BIN1 mutants linked to myopathies, was rescued when the membrane charge was made more negative. The latter findings also show that cells can control tubulation at their membranes by simply altering the membrane charge and through it, the recruitment of BAR proteins and their interaction partners (e.g. dynamin). Graphical abstract: Image 1 Highlights: In vitro, bridging integrator 1 (BIN1) alone generates t-tubule–like membrane topologies. BIN1 bending of low-curvature membranes is controlled by electrostatics in vitro and in vivo . Dynamin 2, as a representative BIN1 binding partner, is mislocalized in BIN1 membrane bending–deficient conditions.